Digital Libraries and Archives 7th Italian Research Conference, IRCDL 2011, Pisa, Italy, January 20-21, 2011. Revised Papers - Agosti, Maristella; Esposito, Floriana; Meghini, Carlo; Orio, Nicola; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed proceedings of the 7th Italian Research Conference on Digital Libraries held in Pisa, Italy, in January 2011. The 20 revised full papers presented were carefully reviewed and cover topics of interest such as system interoperability and data integration; formal and methodological foundations of digital libraries; semantic web and linked data for digital libraries; multilingual information access; digital library infrastructures; metadata creation and management; search engines for digital library systems; evaluation and log data; handling audio/visual and non-traditional objects; user interfaces and visualization; digital library quality.
Keywords: Computer science; Information systems; Database management; Data mining; Information storage and retrieval systems; Computer Science; Information Storage and Retrieval; User Interfaces and Human Computer Interaction; Database Management; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Information Systems and Communication Service